The Human Condition and Technology as Viewed by Selected Contemporary Jewish Thinkers: Danny Schiff and Mois Navon - Klimowicz, Teresa (Roczniki Filozoficzne, 2025)
The purpose of this paper is to analyze the responses to technological challenges formulated by two contemporary Jewish thinkers, Danni Schiff and Mois Navon. The former is a scholar in Jewish ethics and the author of Judaism in a Digital Age, published in 2023. Mois Navon is an Israeli rabbi and philosopher affiliated with Bar Ilan University, working on the problem of the moral status of artificial intelligence, author of the doctoral dissertation The Moral Status Of Artificial Intelligence – A Jewish Ethical Perspective (2024), and founder of an autonomous vehicle software company called Mobileye. Their opinions were framed within the discussion of posthumanism and presented on two levels: anthropological, answering questions about how Jewish thought deals with defining the status of humans in the world; and ethical, dealing with recommendations related to the relationship of humans to technological innovations.